EKSISTENSI PENGADILAN PAJAK DALAM SISTEM PERADILAN DI INDONESIA - Amelia Ayu Paramitha (Pascasarjana Ilmu Hukum, Universitas Widyagama Malang, 2017)
That tax is a transfer from the private sector to the government sector with no direct repayment, so more than 70% of the State’s revenues are derived from tax collection. With a self-assessment system in which the taxpayer is given trust to calculate his own tax amount, some gaps occurs in terms of the amount of tax payable and this causes some disputes dealing with the amount of taxes paid either by fiscus (tax collector) with that of the taxpayer. Therefore, disputes arise bout the amount of outstanding taxes that outstanding. To settle the tax disputes a separate judicial body that will resolve the settlement of the tax dispute is required. The existence of the Tax Court occupies a special place in the structure of the judicial organization, although initially the presence of the tax court becomes a matter of whether the tax court can be classified as a judicial institution, considering that in the tax law court, the Law No.14 of 2002 on Tax Court does not contain and explain clearly the position of the tax court. However, the status of the Court of Taxation is special under the administrative court of the State as affirmed in Article 9 A of Law Number 51 Year 2009 on State Administrative Court. So it is quite clear that the tax court is one part of the judicial system in Indonesia. Keywords: Existence, Tax Court, Judicature.